Macrophage C/EBPδ Drives Gemcitabine, but Not 5-FU or Paclitaxel, Resistance of Pancreatic Cancer Cells in a Deoxycytidine-Dependent Manner - C. Arnold Spek; Hella L. Aberson; JanWillem Duitman (Biomedicines, 2022)
Treatment of pancreatic ductal adenocarcinoma (PDAC), a dismal disease with poor survival rates, is hampered by the high prevalence of chemotherapy resistance. Resistance is accompanied by macrophage infiltration into the tumor microenvironment, and infiltrated macrophages are key players in chemotherapy resistance. In the current manuscript, we identify CCAAT/enhancer-binding protein delta (C/EBPδ) as an important transcription factor driving macrophage-dependent gemcitabine resistance. We show that conditioned medium obtained from wild type macrophages largely diminishes gemcitabine-induced cytotoxicity of PDAC cells, whereas conditioned medium obtained from C/EBPδ-deficient macrophages only minimally affects gemcitabine-induced PDAC cell death. Subsequent analysis of RNA-Seq data identified the pyrimidine metabolism pathway amongst the most significant pathways down-regulated in C/EBPδ-deficient macrophages and size filtration experiments indeed showed that the low molecular weight and free metabolite fraction most effectively induced gemcitabine resistance. In line with a role for pyrimidines, we next show that supplementing macrophage conditioned medium with deoxycytidine overruled the effect of macrophage conditioned media on gemcitabine resistance. Consistently, macrophage C/EBPδ-dependent resistance is specific for gemcitabine and does not affect paclitaxel or 5-FU-induced cytotoxicity. Overall, we thus show that C/EBPδ-dependent deoxycytidine biosynthesis in macrophages induces gemcitabine resistance of pancreatic cancer cells.